IMPROVING STUDENTS’ MOTIVATION IN WRITING DESCRIPTIVE TEXTS BY USING MIND MAPPING - Agus Rafii (IAIN Syekh Nurjati Cirebon, 2017)
This research was Classroom Action Research, it means that in this research as the classroom lecturers and asked one collaborator worked together in planning the action, implementing, observing, and reflecting the action. The results of the study concluded that, the implementation of the Mind Mapping Technique in the teaching of writing descriptive text could develop the ability and improve the motivation of the Third Semester Students of English Department in writing descriptive texts. Based on the finding of this study, the result of the students’ writing from the pre – cycle to cycle 1 increased 2.96%, from cycle 1 to cycle 2 increased 3.95%, and from cycle 2 to cycle 3 increased 5.26%. It means that from initial condition to the third cycle had shown significant results. The result of the students’ motivation from the pre – cycle pre – cycle to cycle 1 increased 9.42%. From cycle 1 to cycle 2 increased 5.68%, and from cycle 2 to cycle 3 increased 10.58%. It means that the implementation of the Mind Mapping Technique could improve the students’ motivation. Keywords: Motivation, Writing, Descriptive Text, Mind Mapping Technique